Protocolo para Emissão de Assinatura Digital utilizando Compartilhamento de Segredo - Pereira, Winicius (2011)
The Internet has enabled the creation of many virtual services in favor of agility, comfort and ease for Brazilian citizens. It is a public environment, in which hundreds of thousands of data are transmitted at all times. But some of these services require that the information provided meet certain safety requirements, such as: the authenticity, confidentiality, integrity and denial, as is the case of digital services provided by notaries in Brazil. The digital signature ensures that these requirements are met even in a complex environment like the Internet. However, it has vulnerabilities that can be explored, such as storing the same in a single device. If the device that stores the user s secret key is stolen or corrupted by an attacker, that can issue a valid subscription like the owner of the signature. Due to this type of problem, the notary digital, does not provide the digital analogue of several procedures, such as the notarization with authenticity in an electronic document. This thesis, therefore, proposes a protocol for issuing a shared digital signature, in which the secret key is divided into parts and stored in dierent devices. To illustrate its use is considered the problem of issuing a digital signature on a deed of purchase and sale of a property with notarization and authentication. The digital signature scheme RSA was used, dividing the user s secret key using the concept of sharing secrets threshold. The protocol is based on the idea that the secret key should not be stored in a single user device. To increase your safety, only a portion of the private key is stored in the user s device. It is also considered the signature of the witnesses in the document, that they attest to the existence of the business. But, should not be able to form a valid signature alone. Moreover, as the agencies of notary public are organ that recognize and authenticate documents, they should also have their share of responsibility in issuing a digital signature by authenticity and the private key storage.